2000
DOI: 10.1017/s1355838200000728
|View full text |Cite
|
Sign up to set email alerts
|

The human coronavirus 229E superfamily 1 helicase has RNA and DNA duplex-unwinding activities with 5′-to-3′ polarity

Abstract: The human coronavirus 229E replicase gene encodes a protein, p66 HEL , that contains a putative zinc finger structure linked to a putative superfamily (SF) 1 helicase. A histidine-tagged form of this protein, HEL, was expressed using baculovirus vectors in insect cells. The purified recombinant protein had in vitro ATPase activity that was strongly stimulated by poly(U), poly(dT), poly(C), and poly(dA), but not by poly(G). The recombinant protein also had both RNA and DNA duplex-unwinding activities with 59-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
181
1
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(197 citation statements)
references
References 68 publications
(18 reference statements)
8
181
1
2
Order By: Relevance
“…This is consistent with the previously characterized HCoV-229E helicase (Seybert et al, 2000a), which also had revealed a high promiscuity with respect to the substrates used. Thus, both DNA and RNA duplexes were found to be unwound by the HCoV-229E helicase with similar efficiency and all types of nucleotide and ribonucleotide cofactors were used (Seybert et al, 2000a;K. A. Ivanov, V. Thiel & J. Ziebuhr, unpublished data).…”
Section: Essential Proteins Involved In Replication and Transcriptionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with the previously characterized HCoV-229E helicase (Seybert et al, 2000a), which also had revealed a high promiscuity with respect to the substrates used. Thus, both DNA and RNA duplexes were found to be unwound by the HCoV-229E helicase with similar efficiency and all types of nucleotide and ribonucleotide cofactors were used (Seybert et al, 2000a;K. A. Ivanov, V. Thiel & J. Ziebuhr, unpublished data).…”
Section: Essential Proteins Involved In Replication and Transcriptionsupporting
confidence: 91%
“…Expression and purification of MBP-HEL and MBP-HEL_KA were done essentially as described for the HCoV-229E helicase . The partially double-stranded DNA substrate used in the unwinding assay was produced by annealing oligonucleotides D2 [59-GGTGCAGCCGCAGCGGTGCTCG-d(pT) 30 -39] and [a-32 P]ATP-labelled D3 [59-d(pT) 30 -CGAGCACCGCTGCGGC-TGCACC-39] as described by Seybert et al (2000a). The unwinding reaction was done for 30 min at 25 uC in buffer A (HEPES/KOH, pH 7?4, 10 % glycerol, 5 mM magnesium acetate, 2 mM dithiothreitol and 0?1 mg BSA ml 21 ) using 10 nM of substrate and various concentrations of MBP-HEL (8, 80 and 800 nM) and MBP-HEL_ KA (800 nM), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The fact that ATP is a competitive inhibitor of the RTPase reaction catalyzed by SARS helicase suggests that the RNA is hydrolyzed at the same active site used to fuel helicase movement [54]. A similar RTPase that plays a role in CAP formation was also found in the SF1 helicase encoded by bamboo mosaic virus [55] In addition to the SF1 helicase motifs, SARS-CoV nsp13 protein, and its relatives from human coronavirus 229E [56] and equine arteritis virus [57], all contain a cysteine-rich zinc binding domain located at their N-termini. Zinc binding domains have been found linked to other helicases and they are frequently found in proteins that interact intimately with nucleic acids.…”
Section: Sars Coronavirus Helicasementioning
confidence: 99%
“…Translation of both ORFs results in the synthesis of two polyproteins that are processed by viral proteinases to release the components of the replication-transcription complex (36,37). Besides containing RNA-dependent RNA polymerase, RNA helicase, and proteases (4,12,15,23,37), which are all common to positive-strand RNA viruses, the CoV replicase was recently predicted to contain a variety of RNA-processing enzymes that are extremely rare or absent in other RNA viruses, including endoribonuclease (NendoU), 3Ј-to-5Ј exoribonuclease (ExoN), 2Ј-O-ribose methyltransferase (2Ј-O-MT), ADP ribose 1ЈЈ-phosphatase, and, in a subset of group 2 coronaviruses, cyclic phosphodiesterase (25, 36). These enzymatic activities might be involved in the replication of the largest known RNA virus genome and in the production of an extensive set of 5Ј-and 3Ј-coterminal subgenomic RNAs (11,14,25,36).…”
mentioning
confidence: 99%